The fourth industrial revolution: realigning the real and digital economies - Esposito, Mark (Henry Stewart Talks, 2022)
Technological diffusion, Multi-stakeholder innovation, Digital protectionism, Invasive business model, Digital platforms, Market inefficiency, Digital economy, Real economy, Disproportionate valuation, Government subsidies, Digital transformation, Technology governance, Collaboration, Scaling out